A Command as the Implementation of Exercitives Illocutionary Acts in the Movie “Abominable” Directed By Jill Culton (Jurnal Pustaka, 2025)
This study entitled A Command as the Implementation of Exercitives Illocutionary Acts in the Movie “Abominable” Directed By Jill Culton is aimed at finding out one type of exercitives illocutionary acts uttered by the characters in the movie; command. It is also analyzed about the effects of the utterances of exercitives illocutionary act based on the context of the situation. The data of this study were taken from an American computer-animated adventure movie entitled Abominable directed by Jill Culton. The data were collected by documentation method through note taking technique, used a qualitative method to analyze the data, and the word-based-form method was used to present data analysis. The theory speech acts proposed by Austin (1962) was used to identify one of the types of exercitive illocutionary acts; command. While, the theory about the ethnography of communication proposed by Hymes (1972) was used to analyze the intended meaning and the perlocutionary acts of the utterances. The results of this study shows that there are 10 utterances categorised as a command which uttered by the characters in the Abominable movie. Meanwhile, the intended meaning and the effect of the utterances can be seen through eight elements of the ethnography of communication, such as setting and scene, participants, ends, act sequence, key, instrumentalities, norms, and genre. These elements of the situation support grasping the real meanings of the characters’ desire to have the hearer take kinds of action.